The effect of oral creatine supplementation on the 1000-m performance of competitive rowers - Rossiter, H. B.; Cannell, E. R.; Jakeman, P. M. (Journal of Sports Sciences, 1996)
his study investigated the change in 1000-m simulated rowing performance in two matched groups of 19 competitive rowers following a 5-day period of supplementation with placebo (CON group) or creatine at a dose equivalent to 0.25 g creatine monohydrate per kilogram of body mass (BM) (EXP group). Creatine uptake was calculated from the difference between the amount fed and the amount recovered in urine during each 24-h period of supplementation. Total creatine uptake .0 (range 22.6±56.6) mmol kg dry weight-1 for these subjects. After supplementation with placebo, the CON group showed no change in 1000-m rowing performance (214.0 ± 30.9 vs 214.1 ± 31.5 s; P = 0.88). Of these subjects, 7 decreased and 10 increased their performance times (range - 3.1 to 2.7%). By contrast, 16 of the 19 subjects in the EXP group improved their performance times. The mean improvement in rowing performance for the EXP group was 2.3 s (211.0 ± 21.5 vs 208.7 ± 21.8 s; P < 0.001), an overall improvement of just over 1% (range - 0.4 to 3.4%). We conclude that in competitive rowers, a 5-day period of creatine supplementation was effective in raising whole-body creatine stores, the magnitude of which provided a positive, though statistically non-significant (r = 0.426, P = 0.088), relationship with 1000-m rowing performance.